Dazhbog: The Ancient Slavic Pagan Deity of the Shining Sky - Oleg Vladislavovich Kutarev (Studia mythologica Slavica, 2021)
The paper is concerned with a detailed consideration of one of the most well-known and frequently mentioned Slavic pagan deities: Dazhbog (or Daž(d)bog). Historiographic stereotypes full of contradictions and problems have been fixed in research concerned with the deity, for example, defining Dazhbog as the deity of the sun; its proximity to another solar deity (Chors) and vagueness, why are there two solar deities; Dazhbog’s relation to the deity Svarog/Svarozhich; Dazhbog’s belonging only to the East Slavic area; the etymology of his name as a “giving deity”. An alternative view on Dazhbog (overlooked rather than new) that can solve these problems is given in this paper.